Elaboração de gibi como instrumento de educação celíaca - SIMÕES, Amanda Antunes Lucas (2023)
Raising awareness about celiac disease is directly related to the quality of life of celiacs. Celiac and celiac caregivers are routinely misunderstood for adopting strict glutenfree diets. This lack of empathy is directly related to emotional problems, social exclusion and depression. This work aimed to develop a comic book with a celiac theme to sensitize children and adults, generating a more empathic attitude towards the celiac condition. This work was approved by the Ethics Committee of the Federal University of Pará (n° 899,717). For the construction of the script, an online questionnaire was created to collect stories experienced by celiacs that they deemed important to be contacted in the comic book format. The answers were transcribed to Excel to select the themes that would be considered in the script, after the script was built, it was sent to a cartoonist. A fictional character was created (Lina) to package the plot of the comic book. A total of 39 depositions were collected, with themes ranging from diagnostic situations to social life. The comic was organized into 7 episodes (Lina and her discovery; visit to the nutritionist; changes; birthday party; go to the supermarket; I want to stay home; Mom's graduation), which narrated the difficult diagnosis, the steps to confirm the disease , the details when buying food in supermarkets and restaurants, the frustrations and difficulties and some routine situations in birthday parties. The final structure of the comic book consisted of 80 figures and 20 pages, paper size a3. We can conclude that sharing real stories is an interesting way to disseminate information and since they are real, the impact on empathy ends up being more positive. The comic book's narrative provides the reader with an approach to celiac reality, showing that such common and simple currently situations can be a torment in the life of celiac patients and their family unit and that we can help them in this disease management with positive and empathetic attitudes.